First-principle study of new insights on the magnetic mechanism of ZnO through rare-earth Nd doping and Zn vacancies. (June 2022) - Hou, Qingyu; Yang, Airong; Zhao, Chunwang
Abstract: Theoretical and experimental studies on the magnetic mechanism of Nd doping or Nd doping and Zn vacancies on ZnO have been reported. However, the magnetic source and mechanism of the doping system are controversial. Thus far, no reasonable theoretical explanation exists. First principles can solve such problems. In this study, the first principles are used to investigate the influence of Nd doping or Nd doping and Zn vacancies on the magnetic source and mechanism of ZnO based on the generalized gradient approximation plane wave supersoft pseudopotential method under the framework of spin density functional theory. The calculation results show that the formation energy of the Zn15 NdO16 system or the Zn14 NdO16 system is smaller and the doping is easier under the O-rich condition than those under the Zn-rich condition. Both doping systems have high binding energy and high stability. The study found that the magnetism of the Zn15 NdO16 system is mainly produced by the spin polarization of the s, p, d, and f states of a single Nd 3+ ion. This phenomenon is consistent with the mechanism by which a single ion in a compound produces magnetism. The magnetism of the Zn14 NdO16 system is produced not only by the double exchange of the p, d, and f state itinerant electrons of a single Nd 3+ ion but also by the d and f state exchange mediated of the O 1− -2 p state itinerant electrons. This finding is consistent with the explanation of the carrier-mediated double exchange mechanism. The new insights on the magnetic origin and mechanism of doped Nd or doped Nd and Zn vacancy coexisting ZnO mediated by itinerant electron have a leading role in studying similar dilute magnetic semiconductors. Graphical Abstract: ga1 Highlights: The first principles are used to study the influence of Nd doping or Nd doping and Zn vacancies on the magnetic source and mechanism of ZnO. The magnetism of the Zn15 NdO16 system is mainly produced by the spin polarization of the s, p, d, and f states of a single Nd 3+ ion. The magnetism of the Zn14 NdO16 system is produced not only by the double exchange of the p, d, and f state itinerant electrons of a single Nd 3+ ion but also by the d and f state exchange mediated by the O 1− -2 p state itinerant electrons.